Characterization of compatibilized blends of nylon 66/poly(2,6-dimethyl-1,4-phenylene ether)/high-impact polystyrene filled with phosphinate-based flame retardants: Mechanical property, rheological behavior, and flame retardancy - Kim, Do Kyun; Song, Kwang Ho; Koo, Chong Min; Hong, Soon Man; Chae, Dong Wook (SAGE PUBLICATIONS LTD, 2015)
The optimum weight ratio of each component in the compatibilized blends of nylon 66/poly(2,6-dimethyl-1,4-phenylene ether)/high-impact polystyrene with polystyrene-co-maleic anhydride and styrene-ethylene-butylene-styrene block copolymer grafted with maleic anhydride was determined in terms of exhibiting balanced mechanical properties. The mechanical strength of the blends was deteriorated with increasing phosphinate-based flame retardant content while the tensile modulus increased. For UL94V test, the addition of approximate to 10wt% phosphinate did not have a significant effect on the flame retardancy showing V2 grade while further addition gave rise to char formation resulting in V0 grade. Limiting oxygen index values increased greatly by ca. 34% at 5wt% phosphinate, followed by mild increase by further addition. Heat release rate peaks of the blends were reduced and broadened with increasing phosphinate content showing little difference from 15wt%. The complex viscosity increased with phosphinate content, but its increasing extent decreased at a high frequency. In the Cole-Cole plot, the presence of the phosphinate shifted the plot from unfilled blends without showing a single master curve depending on its loading level.
Keywords: FIRE RETARDATION; POLYMER BLENDS; OXIDE); POLYAMIDE-6; MORPHOLOGY; PERFORMANCE; COMBUSTION